The spiritual formation, mentoring and peer learning of emerging pastoral leaders - Baldwin, Stephen C. (Stephen Conner), 1950- (2012)
1 online resource (1 PDF (viii, 177 leaves)); Typescript; Includes abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2012; Bibliography: leaves 169-177